2015
DOI: 10.1021/np501058b
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive C21 Steroidal Glycosides from the Roots of Cynanchum otophyllum That Suppress the Seizure-like Locomotor Activity of Zebrafish Caused by Pentylenetetrazole

Abstract: Six new C21 steroidal glycosides, cynotophyllosides A-F (1-6), together with 16 known compounds, were isolated from the roots of Cynanchum otophyllum. The structures of the new compounds were elucidated by spectroscopic analysis and chemical methods. The three major components, otophylloside F (15), otophylloside B (17), and rostratamine 3-O-β-D-oleandropyranosyl-(1→4)-β-D-cymaropyranosyl-(1→4)-β-D-cymaropyranoside (18), suppressed the seizure-like locomotor activity caused by pentylenetetrazole in zebrafish. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
63
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 37 publications
7
63
0
Order By: Relevance
“…Analysis of its 13 C NMR, 1 H− 1 H COSY, HSQC, and HMBC spectra showed the aglycone of 6 to be qingyangshengenin. 24 Two anomeric proton signals at δ H 4.95 (1H, dd, J = 2.1, 9.8 Hz) and 4.56 (1H, dd, J = 2.1, 9.8 Hz) corresponding to two anomeric carbon signals at δ C 95.9 and 100.5 revealed that 6 contained two saccharide moieties with β glycosidic linkages. (Tables 2 and 3), which is in accordance with the molecular mass difference of 14 amu between 9 and 8.…”
Section: Journal Of Natural Productsmentioning
confidence: 98%
See 3 more Smart Citations
“…Analysis of its 13 C NMR, 1 H− 1 H COSY, HSQC, and HMBC spectra showed the aglycone of 6 to be qingyangshengenin. 24 Two anomeric proton signals at δ H 4.95 (1H, dd, J = 2.1, 9.8 Hz) and 4.56 (1H, dd, J = 2.1, 9.8 Hz) corresponding to two anomeric carbon signals at δ C 95.9 and 100.5 revealed that 6 contained two saccharide moieties with β glycosidic linkages. (Tables 2 and 3), which is in accordance with the molecular mass difference of 14 amu between 9 and 8.…”
Section: Journal Of Natural Productsmentioning
confidence: 98%
“…24,27 Thus, 4 was characterized as caudatin 3-O-α-L-diginopyranosyl-(1→4)-β-D-cymaropyranoside. Compound 5 gave a sodium adduct ion at m/z 835.4464 in the HRTOFMS, revealing its molecular formula to be C 42 H 68 O 15 .…”
Section: Journal Of Natural Productsmentioning
confidence: 99%
See 2 more Smart Citations
“…To facilitate a better understanding of epilepsy, zebrafish models of epilepsy have been created by administering pentetrazol to induce seizures (Table 1D). Studies that utilize this method have investigated potential therapeutic compounds to alleviate seizure states as well as to understand changes in gene expression due to seizure events (Barbalho et al 2016; Li et al 2015; Siebel et al 2015). PD is a neurodegenerative disease that results from the loss of dopaminergic cells in the brain (Beitz 2014; Pienaar et al 2010).…”
Section: Zfin As a Resource For Zebrafish Translational Researchmentioning
confidence: 99%